Triple bridge of mechanical circulatory support to heart transplantation listing: A case report. (March 2019) - El-Sayed Ahmed, Magdy M; Thomas, Mathew; Jacob, Samuel; Makey, Ian A; Landolfo, Kevin P; Pham, Si M; Belli, Erol V
A 60-year-old male patient presented to an outside hospital with severe cardiogenic shock. A triple bridge of mechanical circulatory support was utilized to transition him to heart transplantation listing. Initially, coronary artery disease was percutaneously treated and Impella 2.5 was used as mechanical circulatory support for 5 days followed by the second Impella 2.5 for 4 days. Veno-arterial extracorporeal membrane oxygenation support was deployed for 16 days. This was exchanged for HeartWare ventricular assist device support as the third stage of mechanical circulatory support to heart transplantation listing. The patient experienced acute renal failure which was managed by continuous renal replacement therapy then intermittent hemodialysis with eventual complete recovery of the renal function. He was discharged home 56 days after HeartWare ventricular assist device implantation with stable hemodynamic, intact neurologic status and fully recovered renal function. Currently, the patient is listed for heart transplantation.